STATE HIGH SCHOOL STUDENTS IN TASIKMALAYA CITY ARE ASSESSED BASED ON THEIR INTEREST CLASS (NATURAL SCIENCES/SOCIAL SCIENCES) - Amarulloh, Sandy Ihsan; Madawistama, Sri Tirto; Yulianto, Eko (Journal of Authentic Research on Mathematics Education (JARME), 2026)
This study aims to determine the profile of students' mathematics anxiety based on the chosen elective class. The method used in this study is a survey method with data collection techniques involving observation (interviews or questionnaires). Participants were grade XI students of Public Senior High Schools in Tasikmalaya City in the 2023/2024 academic year, totaling 10 schools. The sample consisted of two classes from each school, consisting of one class specializing in science and one class specializing in social studies, selected using a purposive sampling technique. The instrument used was a mathematics anxiety questionnaire. Data processing techniques involved descriptive statistical analysis using Ms. Excel Nvivo version 14. The results of the study showed that there were differences in anxiety between students in science and social studies elective classes. The impression from these findings is the need for special interventions in the mathematics learning process in social studies classes to reduce mathematics anxiety.